CARDIAC TAMPONADE DUE TO RUPTURED MYOCARDIAL INFARCT IN A CASE OF DROWNING: WHETHER NATURAL OR UNNATURAL DEATH? (Journal of Forensic Medicine & Toxicology, 2024)
Drowning and cardiac tamponade secondary to ruptured myocardial infarct are independent cause of death commonly found in routine postmortems. But combination of these causes of death in a single case is rare. Here we are presenting a case of a cardiac tamponade due to pathological ruptured myocardial infarction with subsequent accidental fall in the water tank leading to death by drowning. In such case, the manner of death is natural or accidental is the point of issue which may arise in minds of investigating agency, insurance personnel and the relatives of the deceased.
Keywords: Drowning; Cardiac tamponade; Combined death; Manner of death